2017 Physics Education Research Conference Proceedings 2018
DOI: 10.1119/perc.2017.pr.054
|View full text |Cite
|
Sign up to set email alerts
|

Examining students’ perceptions of innovation and entrepreneurship in physics

Abstract: The joint AAPT and APS PHYS21 report emphasizes preparing students for diverse career paths, including the need for more opportunities to learn innovation and entrepreneurship in physics. To support these changes, research is needed on students' interest and perceptions of innovation and entrepreneurship, and suggestions for integration into the undergraduate physics experience. We conducted semi-structured focus groups with 20 physics majors around several concepts related to innovation and entrepreneurship: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Additional research in students' attitudes and perceptions about the skills and nature of physics supports this finding. Research from Leak et al identifies some of the common attitudes and perceptions students have as to what it is like to be a physicist, as well as what skills are important to physics [17,18]. Leak et al asked: What do students emphasize when asked to describe physics to a high school student considering majoring in physics?…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional research in students' attitudes and perceptions about the skills and nature of physics supports this finding. Research from Leak et al identifies some of the common attitudes and perceptions students have as to what it is like to be a physicist, as well as what skills are important to physics [17,18]. Leak et al asked: What do students emphasize when asked to describe physics to a high school student considering majoring in physics?…”
Section: Discussionmentioning
confidence: 99%
“…Leak et al asked: What do students emphasize when asked to describe physics to a high school student considering majoring in physics? It was found that some of the emphasized details were things like "learn how the universe works," "learn how to learn," " have a passion for physics," and "gain flexible skill-sets" [17,18]. All of these focus on physics being about ideas rather than applications that help people and contribute to society.…”
Section: Discussionmentioning
confidence: 99%
“…The PIPELINE Network Project Despite the potential benefits of incorporating PIE elements into physics programs, there are many reasons departments are slow to adopt these strategies. These include a lack of awareness of actual employment outcomes for physics graduates (and therefore an understanding of the need for efforts which prepare students for non-academic career paths), a lack of institutional support for such efforts, an uncomfortable feeling of unfamiliarity with entrepreneurial concepts, and a lack of existing, tested PIE curricula that could be easily adapted to fit within their department's unique landscape of resources and constraints (including being integrated into existing physics coursework) [23].…”
Section: Physics Innovation and Entrepreneurship Education (Pie): A Dmentioning
confidence: 99%
“…technology, communication, creativity) but others (design, business) as being unimportant to physics and more closely related to other fields (e.g. business or engineering) [23].…”
Section: Research Outcomesmentioning
confidence: 99%